PENINGKATAN KOMPETENSI PENGGUNA SISTEM INFORMASI AKUNTANSI KEUANGAN PADA SEKOLAH MUHAMMADIYAH DI BUKIT KECIL KOTA PALEMBANG - Siddik, Sa’ada; Welly, Welly; Rama Ningsih , Ayu (Universitas katolik Musi Charitas, 2020)
Partners in the implementation of community service are Muhammadiyah 2 Middle School, Muhammadiyah 1 Aliyah Madrasah School, Muhammadiyah 2 Middle School, Muhammadiyah 1 Tsanawiah Madrasah School and Muhammadiayah Elementary School 1. These schools are under the supervision of the Muhammadiyah Bukit Kecil Branch Palembang. Based on the analysis of the situation, it can be identified several problems faced by partners such as the knowledge possessed by the school treasurer in the use of accounting information systems, and the process of preparing financial statements is also very limited. The service implementation method consists of two stages. The first, step is to arrange material, namely basic accounting and accounting information systems. The second stage conducts training and coaching, to producing financial reports. Results and discussion, community service activities are carried out by means of training and assistance. The community service activities were carried out for the five partners, also involved a treasurer of the Palembang Muhammadiyah Branch Manager. This activity began with conducting a field survey for the stage of preparing the work plan. This activity resulted in an agreement with the principal included in the partner and the Muhammadiyah Palembang Branch Manager, which conducted training on the preparation of financial statements, and trained to develop potential treasurers using the school's financial accounting information system. The conclusions of community service activities are as follows: a) has been running well and smoothly, b) increasing the ability of treasurers of the Muhammadiyah School in Bukit Kecil to use accounting information systems and compile school financial reports..